State-owned commercial banks - Ugo Panizza (Graduate Institute of International and Development Studies, 2021)
This paper builds a new dataset on bank ownership and reassesses the links between state-ownership of banks and each of financial development, economic growth, financial stability, bank performance, liquidity creation, and lending cyclicality. Using panel data to estimate the short-and medium-term relationship between state-ownership and financial depth, the paper shows that there is no robust correlation between these two variables. The paper also finds no evidence of a negative correlation between state-ownership of banks and economic growth (if anything, the relationship is positive but rarely statistically significant). Looking at financial instability, the paper finds that banking crises predict increases in state-ownership but that there is no evidence that high state-ownership predicts banking crises. Focusing on bank performance, the paper shows that data for the period 1995-2009 are consistent with existing evidence that state owned banks are less profitable than their private counterparts in emerging and developing economies. However, more recent data show no difference between the profitability of private and public banks located in emerging and developing economies. The paper also corroborates the existing literature which shows that in emerging and developing economies lending by state-owned banks is less procyclical than private bank lending. Exploring the role of fiscal fundamentals, the paper does not find any difference in countercyclicality between high and low debt countries, but it finds that countercyclical lending by state-owned banks substitutes, rather than complement, countercyclical fiscal policy. It also finds that lending by state-owned banks helps smoothing production in labor intensive industries and in industries with a large share of small firms.
Keywords: G21; H11; O16; 330; Banking; State-owned banks; Financial stability